The Effectiveness of a Training Program Based on Using Technology in Developing Sensory Synergy for Autistic Children at Intellectual Education and Autism Institutes in Taif - Alkenani, Reem Abduallah Mohamad; Bashatwa, Mohamad Othman (Journal of Curriculum and Teaching Methodology, 2022)
The current study aims to identify the effectiveness of training program based on using technology in developing some sensory synergy skills forautistic children, where both researchers used the Empirical research because it is relevance to the nature of this study , and to achieve the study goal, both researchers prepared the training program consists of 14 training hours of electronic programs, the sensory synergy scale was prepared after reviewing previous studies, the scale consists of 12 items. The prior and post measurements were used on the study sample consisting of (21) students with autism disorder (simple - and moderate) affiliated with the Intellectual Education and Autism Institute in Taif. The study has concluded several results, the most notably is the differences between the degrees of disability (simple/moderate) in the effectiveness of the training program by using modern technology to develop sensory synergistic skills among autism children, there were differences in the effectiveness of training program in developing the skill of attention and visual communication, there were differences in the effectiveness of training program in developing the skill of expressing feelings and emotions clearly among students with autism spectrum disorder and there are differences in the effectiveness of training program in developing the skill of telling other students what they feel or what they need. Both researchers recommended for the necessity of training employees with autism disorder children on some skills to deal with them properly, and to help them participate actively and effectively.